Integrating the social utilization status of ecological assets for spatial optimization management: a comprehensive framework - Ren, Xiaoyan; Yan, Fengying (Frontiers in Ecology and Evolution, 2024)
Sustainable spatial planning increasingly emphasizes the protection and restoration provided by nature to human welfare, yet scientifically assessing and managing the societal utilization status of natural ecological assets (EAs) remains a challenge. This study introduces a novel classification of EAs based on the degree of dependency of human societies, and establishes an assessment framework for the spatial utilization status of EAs, incorporating indicators related to “pattern-quality-supply-demand-risk”. These indicators are integrated into the construction of ecological security patterns to optimize the management of EAs. Validated in Changxing County, Zhejiang Province, China, key findings include: (1) In 2020, the EAs of Changxing provided a value of CNY 77.936 billion, with livable climate assets dominating and carbon assets least prevalent. (2) Urban development has led to EA loss, with the most significant losses in high-supply areas and the highest loss risks in areas with scarce EAs, yet maintaining an overall balance of supply and demand. (3) In 2020, the total area of EA sources in Changxing was 487.34 km², accounting for 34% of the total land area, with 42.34% classified as high-security zones and 11.21% as high-alert zones. This study proposes an approach to ecological spatial optimization management that integrates the spatial utilization status of EAs, providing planners with practical tools and illustrative cases for seamlessly incorporating localized ecological elements into spatial planning. Our research applies to regions facing challenges related to EA loss and striving for sustainable development, offering strategies for ecological restoration, compensation, and optimization management.